2021
DOI: 10.1080/21711976.2021.1954439
|View full text |Cite
|
Sign up to set email alerts
|

Tropical climate influences affects, sensation of fatigue and environmental perceptions (El clima tropical influye sobre los afectos, la sensación de fatiga y las percepciones del medio ambiente)

Abstract: The current experimental study evaluated how a tropical climate (i.e., wet and hot environment) influences positive and negative affects, sensation of fatigue and environmental perceptions (i.e., comfort and thermal sensations). A convenience sampling of students (30 females and 30 males, M age = 21.94 years, age range: 19-28 years) who lived all the year in the French West Indies performed two conditions in Tropical Climate (TC) and in Neutral Climate (NC), counterbalanced. During each climate condition, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…However, they did not consider the individual perception of the environment (e.g., comfort and thermal sensations) nor related psychological factors (e.g., affect and perceived fatigue), which were expected to be affected by a TC as well and to further negatively impact cognitive performance [44]. In a second separate study, Robin et al [34] showed that TCs contributed to a decrease in positive affect and thermal comfort scores and further increased fatigue and thermal sensation scores. They argued that it was certainly more pleasant for participants to be in a NC than in a TC before engaging in a MI task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they did not consider the individual perception of the environment (e.g., comfort and thermal sensations) nor related psychological factors (e.g., affect and perceived fatigue), which were expected to be affected by a TC as well and to further negatively impact cognitive performance [44]. In a second separate study, Robin et al [34] showed that TCs contributed to a decrease in positive affect and thermal comfort scores and further increased fatigue and thermal sensation scores. They argued that it was certainly more pleasant for participants to be in a NC than in a TC before engaging in a MI task.…”
Section: Discussionmentioning
confidence: 99%
“…Both imagery vividness and ease, as well as the ability to achieve temporal congruence, were found to be negatively impacted compared to MI performed in a neutral climate (NC) [30,31]. TC is characterized by high average temperatures (≈27 • C) and hygrometry levels (more than 75% relative humidity in the air) that exceed evapotranspiration capacities and negatively impact motor and cognitive performances [32,33], as well as thermal comfort and perceived fatigue [34]. Over the course of the day, temperatures in a TC can range from 24 • C (±1 • C) in the early morning and evening, to over 31 • C (±2 • C) between 10 a.m. and 3 p.m. [35].…”
Section: Of 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of Watson et al (1988) despite of mentioning the concerns and limitations that could have obstructed individuals from feeling openly happy and revitalized indicate that results were presented being related to negative aspects that diminished in the experience group like reducing emotions (e.g., anguish, guilt, aggressiveness, and irritability). In Guadeloupe, Robin et al (2021) measured positive and negative aspects after being in a natural zone aiming to discover the emotional effects of being surrounded by a tropical environment, also an innovative setting where nature connectedness was assessed, presenting a climate with humid weather characteristics. Although they found that participants indicated negative feelings (e.g., fatigue, discomfort) after being surrounded by this climate, generating unpleasant emotions on people.…”
Section: Discussionmentioning
confidence: 99%
“…De même, [18] ont montré que l'augmentation de la ventilation en condition de TE pouvait réduire le flux sanguin cérébral ce qui pouvait impacter négativement les processus d'élimination de la chaleur au niveau du cerveau et engendrer une contrainte cognitive supplémentaire pouvant nuire au traitement de certaines tâches cognitives complexes [19,20] et favoriser l'apparition de fatigue mentale [21]. De plus, et comparativement à un environnement dans lequel la température est neutre, une TE peut altérer l'état émotionnel [2 2], diminuer le confort thermique [11,23] ou augmenter les affects négatifs tels que la colère ou l'agressivité [24].…”
Section: Conséquences D'une Température Elevéeunclassified